Educational program in oral health for caregivers on the oral hygiene of dependent elders - Jéssica Damares LAGO; Laiza Maria Grassi FAIS; Andréia Affonso Barretto MONTANDON; Lígia Antunes Pereira PINELLI
Abstract Objective Due increased number of elders living in long-term care institutions, actions designs to improve their oral health are essential. Thus, the aim of this study was to evaluate the impact of an educational program for the caregivers through the assessment of the oral hygiene of institutionalized elders. Material and method The education program consisted in lectures to caregivers about oral health that were performed once a month. The subjects were 40 functionally dependent institutionalized elders and 14 caregivers. Hygiene habits, plaque index, and tongue coating/discoloration of the elders were measured before the educational program (baseline- T0) and after 6 (T1), 12 (T2), 18 (T3) and 24 months (T4). Caregivers answered questions about their knowledge, doubts and implementation of dental care (T0 to T4). Result After analyzing the data (Friedman, Chi-square and Spearman α = 0.05), a gradual improvement in the oral hygiene of the subjects was observed, with an increased frequency of brushing (p=0.0005), a change in the brush type (p=0.0065) and a reduction in the plaque index (p<0.05) and tongue coating (p<0.05). Caregivers showed a marked improvement in their dental care knowledge. Conclusion It was concluded that the educational program for caregivers had a positive impact in the oral health of institutionalized elderly observed by the increased in the effectiveness of oral hygiene parameters such as plaque index and tongue coating, contributing to the knowledge gain in hygiene by caregivers.